MENELISIK NILAI DAKWAH YANG TERKANDUNG PADA PROSESI PENYELENGGARAAN POHUTU MOPONIKA: MENELISIK NILAI DAKWAH YANG TERKANDUNG PADA PROSESI PENYELENGGARAAN POHUTU MOPONIKA - Putra, Abdur Rahman Adi Saputera (Farabi, 2023)
This research explores the values of da'wah within the marriage tradition of Pohutu Moponika in Gorontalo, serving as a platform for disseminating religious values. It employs a qualitative approach and a case study methodology. Findings indicate that the processes within Pohutu Moponika reflect principles of Islamic teachings and local wisdom, such as justice, balance, communication, mutual understanding, and sincerity in marriage. These processes also highlight other values aligned with Islamic teachings, such as willingness to communicate, etiquette, morality, goodwill, and honesty in interactions. The Pohutu Moponika tradition also encompasses values of cultural preservation, respect for family, commitment, interfaith harmony, and seriousness in marriage. The marriage processes within the Pohutu Moponika tradition serve as an effective medium for actualizing the values of Islamic da'wah in everyday life. These values can strengthen the foundation of families, promoting harmony in accordance with Islamic teachings and the local traditions of Gorontalo society.